1999
DOI: 10.1046/j.1365-2036.1999.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Is maintenance therapy always necessary for patients with ulcerative colitis in remission?

Abstract: Mesalazine prophylaxis is necessary for the prevention of relapse by patients with ulcerative colitis in remission for less than 2 years, but this study casts doubt over whether continuous maintenance treatment is necessary in patients with prolonged clinical, endoscopic and histological remission, who are at very low risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 22 publications
(27 reference statements)
1
56
0
3
Order By: Relevance
“…According to a study by Ardizzone et al (2) , the rate of return for maintenance therapy was 26% per year.…”
Section: Failure In Remissionmentioning
confidence: 99%
“…According to a study by Ardizzone et al (2) , the rate of return for maintenance therapy was 26% per year.…”
Section: Failure In Remissionmentioning
confidence: 99%
“…Although the study of Dissanayake and Truelove [56] suggested that maintenance therapy with 5-ASA should be continued indefinitely, a recent trial by Ardizzone et al [57] found that patients who had maintained their remission on 5-ASA for at least 2 years had no greater risk of relapse if they were randomized to placebo than when they remained on 5-ASA.…”
Section: Maintenance Therapy In Ulcerative Colitismentioning
confidence: 99%
“…Ardizzone et al [61] in a placebo-controlled study evaluated if a maintenance treatment is always necessary according to the length of remission. Patients with longer remission (62 years) showed no differences in the incidence of relapse with or without mesalazine treatment (relapse rate of 18% in the mesalazine group vs. 26% in the placebo group).…”
Section: Maintenance Of Remissionmentioning
confidence: 99%